2009
DOI: 10.5194/angeo-27-1153-2009
|View full text |Cite
|
Sign up to set email alerts
|

Arctic tidal characteristics at Eureka (80° N, 86° W) and Svalbard (78° N, 16° E) for 2006/07: seasonal and longitudinal variations, migrating and non-migrating tides

Abstract: NMT with s=0, +2 (westward) dominate in non-summer months, while for the semi-diurnal tide NMT with s=+1, +3 occur most often during equinoctial or early summer months. These wave numbers are consistent with stationary planetary wave (SPW)-tidal interactions.Assessment of the global topographic forcing and atmospheric propagation of the SPW (S=1, 2) suggests these winter waves of the Northern Hemisphere are associated with the 78-80 • N diurnal NMT, but that the SPW of the Southern Hemisphere winter have littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 33 publications
7
57
0
Order By: Relevance
“…Manson et al, 1988Manson et al, , 1989Manson et al, , 2009Vincent et al, 1988;Avery et al, 1989;Portnyagin et al, 1993;Fraser et al, 1995;Mitchell et al, 2002). At these latitudes the diurnal tidal modes are predominantly trapped, and so in the MLT region the semidiurnal tide has larger amplitudes.…”
Section: R N Davis Et Al: Mesospheric Tides Over Ascension Islandmentioning
confidence: 99%
“…Manson et al, 1988Manson et al, , 1989Manson et al, , 2009Vincent et al, 1988;Avery et al, 1989;Portnyagin et al, 1993;Fraser et al, 1995;Mitchell et al, 2002). At these latitudes the diurnal tidal modes are predominantly trapped, and so in the MLT region the semidiurnal tide has larger amplitudes.…”
Section: R N Davis Et Al: Mesospheric Tides Over Ascension Islandmentioning
confidence: 99%
“…Meteor radars have become valuable tools for probing MLT dynamics, especially in the 1990s and beyond. Over arctic latitudes, studies of mean wind and tides have been carried out using limited data of lengths of typically less than 1-2 years (e.g., Hocking, 2001;Mitchell et al, 2002;Manson et al, 2009) and only a few observations deal with long term observations (Portnyagin et al, 2004;Day and Mitchell et al, 2010). But there are no long term observations such as those made over mid-and low-latitudes (Nakamura et al, 1996;Kishore Kumar et al, 2008, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Manson et al (2009), based upon analysis of the Svalbard and Eureka tides during 2006/2007, showed that at latitudes near 80 • N the semidiurnal MT (s=2) is dominant in summer, while the semidiurnal NMT with s=1 and s=3 occur most often during equinoctial or early summer months. Portnyagin et al (2004) examined the slopes of the tidal phases (time of maximum in UT) versus longitudes and concluded that in the southern • N) the migrating tides are dominant for both diurnal and semidiurnal oscillations during all months, but with some indications of NMT in May-June.…”
Section: Introductionmentioning
confidence: 99%